2000
DOI: 10.1002/pc.10212
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive evaluation methods for damage assessment in fiber‐metal laminates

Abstract: Aerospace Research (IAR) is engaged in a collaborative project with Bombardier Aerospace. The main objective of the project is to evaluate the potential of applNg fiber-metal laminates (FML) to aircraft types manufactured by Bombardier. As a part of this project, nondestructive evaluation (NDE) procedures have been developed and used at IAR to determine the extent of damage caused by impact, corrosion and fatigue loads in a commercial FML material (GLARE). X-rays using radioopaque fluids as well as conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Moreover, the internal impact damage is formed in composite laminates extending well beyond the impacted area, which significantly reduces the strength and stiffness of composite structures. However, research [59][60][61][62] has indicated that GLARE is not susceptible to the formation of large areas of internal damage under impact loading. The internal impact damage in GLARE is mostly confi ned to a relatively small area surrounding the point of impact.…”
Section: Impact Behaviormentioning
confidence: 99%
“…Moreover, the internal impact damage is formed in composite laminates extending well beyond the impacted area, which significantly reduces the strength and stiffness of composite structures. However, research [59][60][61][62] has indicated that GLARE is not susceptible to the formation of large areas of internal damage under impact loading. The internal impact damage in GLARE is mostly confi ned to a relatively small area surrounding the point of impact.…”
Section: Impact Behaviormentioning
confidence: 99%
“…In non-destructive testing of the interface of the metal laminate, ultrasonic speculation method and the transmittance X-ray inspection have been often applied [3,4]; however, an easier and quicker method would be preferable for practical evaluations.…”
Section: Introductionmentioning
confidence: 99%
“…Various inspection methods have proven their effectiveness in the detection of different defects and damages in Glare structures. The most consolidated are based on ultrasonic C-scan inspections [9,[14][15][16][17][18]. Ultrasonic inspections are based on differences in sonic transmission of different materials and reflection on interfaces in laminates.…”
Section: Introductionmentioning
confidence: 99%
“…Among other well-known NDT techniques used in Glare it is worth mentioning ultrasonic Lamb wave propagation [21,22], eddy current testing [13,16], x-ray radiography [16], thermography [23], and shearography [24]. In addition to the different constraints inherited in each single methodology, the common drawback is related to the limitation during in-service operations.…”
Section: Introductionmentioning
confidence: 99%